Future trend of medical design practice in Malaysia: brief perspective of prevailing healthcare facility designs in Malaysia - Mohd Nawawi, Norwina (2015)
Malaysia lies at the cross road of Asia with affordable healthcare services in modern and traditional medicine. The presentation scan through prevailing healthcare design practices in Malaysia covering public and private sector through qualitative analysis in brief. The study aims to provide a glimpse and able to categorised the various influences behind the resultant architecture and design that had landscaped Malaysian healthcare design today for future direction.